Effectiveness of Pyriproxyfen-Controlled Release Block against Larvae of Aedes (Stegomyia) aegypti in Kuala Lumpur, Malaysia - Chen, C.D.; Andy-Tan, W.A.; Loke, S.R.; Lee, H.L.; Yasmin, A.R.; Sofian-Azirun, Mohd (2008)
This study was conducted to evaluate the effect of a commercially available pyriproxyfen, an insect growth regulator (IGR) on the larvae of a dengue vector, Ae. aegypti. The study site was the surrounding area of the Medical Entomology Unit, Institute for Medical Research (IMR), Kuala Lumpur (N03Â°10.167â², E101Â°41.919â²). Pyriproxyfen-controlled release blocks with dosages of 10 w/w and 20 w/w were used to treat a set of earthen jars placed outdoors. Untreated jars were also set up as controls. Fifty laboratory-bred 2nd instar larvae were introduced into each earthen jar and observed daily. The number of adults that emerged was recorded and the larval mortality was calculated. The indicators of effectiveness of IGR for these studies were: (i) duration of effectiveness, and (ii) percentage of emergence inhibition (El). There was a significant difference in the number of emerged adults obtained from the untreated and treated earthen jars up to 25 weeks (p<0.05). The duration of effectiveness of pyriproxyfen caused 80 emergence inhibition in earthen jars treated with 10 w/w and 20 w/w pyriproxyfen up to 22 and 25 weeks, respectively. Pyriproxyfen-controlled release block is an effective method of controlling mosquito larvae for several months. The method of application of the block is simple and straightforward and can therefore be used easily.